The effects of enteric-coated sodium bicarbonate supplementation on 2 km rowing performance in female CrossFit® athletes - Martin, R. A. X. J.; Hilton, N. P.; Sparks, S. A.; Saunders, B.; McNaughton, L. R. (European Journal of Applied Physiology, 2023)
Purpose Sodium bicarbonate (SB) supplementation can improve exercise performance, but few studies consider how effective it is in female athletes. The aim of the study was to establish the effect of individually timed pre-exercise SB ingestion on 2 km rowing time trial (TT) performance in female athletes.